2021
DOI: 10.30607/kvj.898478
|View full text |Cite
|
Sign up to set email alerts
|

Klinik Olarak Pnömoni Tespit Edilen Keçilerde Serum Amiloid-A Düzeylerinin Değerlendirilmesi

Abstract: In this study, 20 goats between the ages of 0-24 months were used. After clinical, systemic, and hematological examinations, goats were divided into two groups. Clinically diagnosed with pneumonia (n=10) were the study group, whereas healthy goats (n=10) were formed as the control group. Auscultation was performed in the clinical examination. Blood samples from Vena jugularis in the hematological study, White Blood Cell (WBC), Red Blood Cell (RBC), Hemoglobin (Hb), Hematocrit (Hct), Mean Corpuscular Volume (MC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…In a study on goats naturally infected with paratuberculosis, SAA concentration was reported to increase (Sevgisunar and Şahinduran, 2021). Demirbas and Kabu (2021) determined in their study on pneumonic goats that SAA concentration was higher in the pneumonic group than the healthy goats. Kabu et al, (2023), SAA and Hp concentrations were found high in lamb with diarrhea due to Cryptosporidium.…”
Section: Resultsmentioning
confidence: 96%
“…In a study on goats naturally infected with paratuberculosis, SAA concentration was reported to increase (Sevgisunar and Şahinduran, 2021). Demirbas and Kabu (2021) determined in their study on pneumonic goats that SAA concentration was higher in the pneumonic group than the healthy goats. Kabu et al, (2023), SAA and Hp concentrations were found high in lamb with diarrhea due to Cryptosporidium.…”
Section: Resultsmentioning
confidence: 96%